Etika Pergaulan Muda Mudi Masa Kini ( Suatu Tinjauan Studi Etika di Universitas Victory Sorong) - Leuwol, Natasya Virginia; Pheter, Christian J.; Mangori, Nelvi; yekwam, Meydelin; Lukman, Erika Patricia (CV. ITTC INDONESIA, 2023)
In the association between humans, both in socialization in society and in organizations, ethics or good manners are always needed, including in the association of today's youth. Ethics is a human problem in general. Wherever humans are in their community, surely ethics and manners play a role as guidelines for good or bad behavior in their association. In this adolescent age, usually in his association, a teenager is very unstable, easily influenced by persuasion, and even a teenager wants to try something new that maybe he doesn't know whether it is good or not. The method used is a qualitative one, which involves describing and making direct observations of young people at Victory University, Sorong. And the research results obtained show, that adolescents need behavioral guidelines so that their associations can run well in accordance with the norms of their society or in accordance with the norms of the religion they adhere to, so that they avoid deviant associations that are not in accordance with societal religious norms. For this reason, religion and faith are the foundations of an individual's life. Without religion, life will be chaotic, because there is no outlook on life. Religion and faith can also shape an individual's personality. With religion, individuals can distinguish between what is good and what is not